Harnessing competitive advantage: A resource-based perspective on sustainable business performance in tourism villages - Iriani, Prof. Dr. Sri Setyo; Dian Anita, Nuswantara; Farid, Pribadi; Puspita Sari, Sukardani; Dwiarko, Nugrohoseno; Reynaldi Dwi, Junianta (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Purpose – This research analyzes the competitive advantage of tourist villages influenced by VRIN and non-VRIN resources on the performance of tourist village businesses. The sporadic nature of village tourism development and the difficulty of getting out of the pioneer level are the problems raised in this study.Design/methodology/approach –This research collected primary data on respondents who were workers from tourist villages, according to the established criteria. A total of 383 research respondents were obtained from distributing questionnaires. Using a quantitative approach, this study analyzed the relationship between VRIN resource and non-VRIN resource variables on competitive advantage, which then affects business performanceFindings – The research of the study shows that VRIN resources significantly influence competitive advantage, which then affects business performance. The results of the study also show that non-VRIN resources do not affect competitive advantage. This shows how VRIN resources play a role in forming the unique value of tourist villages as well as traditional resources that are no longer relevant in forming the competitive advantages of tourist villages.Research limitations/implications – This research has limitations in generalizing the research results, where the research context was only conducted in Indonesia, precisely in East Java. Further research can develop the research by adding the geographical scope of the research sample.Practical implications – This research underlines the importance of strategic development of tourist villages based on a resource-based view approach. Development based on intangible assets, integration, and collaboration with other parties can be done by tourist villages.Originality/value – The use of the resource-based view approach in analyzing the competitive advantage of tourist villages is still not widely used, which then becomes the unique value of this research.